Design Analysis and Determination of Compensation in MSMEs (Case Study on PT. Galunggung Net Tasikmalaya) - Rizqi Syaroh Amaliyah; Lutfi Fauzi Hidayat; Eka Apriliani; Julia Tri Lestari; Noviani Noviani (Eduvest - Journal of Universal Studies, 2025)
Industrial relations in human resource management require a fair and competitive compensation system to balance the interests of employees and employers. However, SMEs like PT. Galunggung Net Tasikmalaya often face challenges in implementing a compensation design that aligns with industry standards and labor regulations. This study aims to analyze the design and determination of compensation at PT. Galunggung Net to understand the challenges in ensuring internal equity and external competitiveness. This research employs a qualitative approach with a case study method, involving interviews with the company's owner and HR personnel. The findings indicate that the compensation system includes direct financial compensation (salaries, allowances, incentives), indirect financial compensation (insurance, facilities), and non-financial compensation (recognition, performance evaluation). However, there are gaps in salary benchmarking, non-compliance with minimum wage standards, and a lack of protection for freelance workers. To enhance fairness and competitiveness, PT. Galunggung Net should conduct benchmarking, refine its performance-based incentive system, and ensure compliance with labor regulations. This study provides insights for SMEs in designing sustainable compensation strategies to improve employee welfare and organizational stability.